Impact of Lactic Acid Bacteria on Immunoreactivity of Oat Beers - Anna Diowksz; Paulina Pawłowska; Edyta Kordialik-Bogacka; Joanna Leszczyńska (Applied Sciences)
The common contamination of oats with gluten cereals represents a problem for celiacs. One way to reduce the level of toxic peptides may be hydrolysis by lactic acid bacteria (LAB). The study examined the influence of the addition of a LAB starter at the grain malting stage on the immunoreactivity of oat beers using enzyme-linked immunosorbent assays with rabbit antibodies and human sera. Immunoblotting was used to identify proteins involved in the immunoenzymatic reaction. The immune response to QQQP and PQQQ sequences was much higher in barley and barley malt (64–76% in relation to wheat) than in oats (20%) and oat malts (below 26%). In the case of anti-QQQPP peptide antibodies, the differences were not so pronounced, mainly due to the high heterogeneity of the oat malt samples. The remaining immunoreactivity was effectively reduced during the technological process of beer production. The mashing process contributed most to the decrease in immunoreactivity, with the wort produced from oat sour malt having an immunoreactivity level of lower than 4%. In the subsequent stages of the beer production process, the immune response was further reduced to below 2% in the resulting beer. Although the level of immunoreactivity of oat sour malt assessed with rabbit antibodies was comparable to that of the regular one, oat sour beers presented significantly weaker immune responses than barley beers, which was not always the case with regular oat beers. This proves the beneficial effect of LAB on reducing the immunoreactivity of the raw material. The analysis performed with human sera confirmed this tendency. Although the immune response to oat beer was strongly dependent on individual sensitivity, the remaining immunoreactivity in oat beers after simulated digestion was only 0.6–2.0%.